Pentamethylquercetin Regulates Lipid Metabolism by Modulating Skeletal Muscle-Adipose Tissue Crosstalk in Obese Mice - Jianzhao Wu; Jingxia Du; Zhi Li; Wei He; Min Wang; Manwen Jin; Lei Yang; Hui Liu (Pharmaceutics, 2022)
Irisin is an exercise-induced hormone that regulates lipid metabolism. The present study investigates whether the anti-obesity effect of the natural flavonoid pentamethylquercetin (PMQ) is related to irisin secretion from skeletal muscle in whole animals and cultured cells. Obese mice induced by monosodium glutamate were administered oral PMQ to determine blood irisin level and in vivo parameters of lipid metabolism, and cultured mouse C2C12 myoblasts and 3T3-L1 preadipocytes were employed to investigate the related molecular identities. PMQ increased circulating irisin and decreased bodyweight, insulin, and lipid levels accompanied with increasing brown-like adipocyte formation in obese mice. The brown adipocyte marker uncoupling protein 1 (UCP-1) and other brown-like adipocyte-specific genes and/or markers were increased in mouse white fat tissue, while PMQ treatment reversed the above changes. PMQ also dose-dependently increased the reduced levels of AMP-activated protein kinase (AMPK), peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α), and fibronectin type III domain-containing 5 (FNDC5) signal molecules in obese mice. Interestingly, the irisin level was increased in the culture medium of C2C12 cells treated with PMQ, and the conditioned medium stimulated the brown-like transition of 3T3-L1 preadipocytes with the increased expression of PGC-1α, FNDC5, UCP-1, and other brown-like adipocyte-specific genes. The effects of conditioned culture medium were abolished in C2C12 cells with silenced PGC-1α. On the other hand, PMQ-induced upregulation of PGC-1α and FNDC5 expression was reduced by AMPK inhibitor Compound C in C2C12 cells. Our results demonstrate the novel information that PMQ-induced irisin secretion from skeletal muscle involves the improvement of metabolic dysfunction in obese mice via activating the AMPK/PGC-1α/FNDC5 signal pathway, suggesting that PMQ modulates skeletal muscle-adipose tissue crosstalk and may be a promising drug candidate for treating obesity and obesity-related metabolic diseases.